The role of recipient myosteatosis in graft and patient survival after deceased donor liver transplantation. Issue 2 (1st February 2021) - Czigany, Zoltan; Kramp, Wiebke; Lurje, Isabella; Miller, Hannah; Bednarsch, Jan; Lang, Sven Arke; Ulmer, Tom Florian; Bruners, Philipp; Strnad, Pavel; Trautwein, Christian; von Websky, Martin Wolfgang; Tacke, Frank; et al.
Abstract: Background: Myosteatosis is associated with perioperative outcomes in orthotopic liver transplantation (OLT). Here, we investigated the effects of body composition and myosteatosis on long‐term graft and patient survival following OLT. Methods: Clinical data from 225 consecutive OLT recipients from a prospective database were retrospectively analysed (May 2010 to December 2017). Computed tomography‐based lumbar skeletal muscle index (SMI) (muscle mass) and mean skeletal muscle radiation attenuation (SM‐RA) (myosteatosis) were calculated using a segmentation tool (3D Slicer). Patients with low skeletal muscle mass (low SMI) and myosteatosis (low SM‐RA) were identified using predefined and validated cut‐off values. Results: The mean donor and recipient age was 55 ± 16 and 54 ± 12 years, respectively. Some 67% of the recipients were male. The probability of graft and patient survival was significantly lower in patients with myosteatosis compared with patients with higher SM‐RA values ( P = 0.011 and P = 0.001, respectively). Low skeletal muscle mass alone was not associated with graft and patient survival ( P = 0.273 and P = 0.278, respectively). Dividing the cohort into quartiles, based on the values of SMI and SM‐RA, resulted in significant differences in patient but not in graft survival ( P = 0.011). Even though multivariable analysis identified low SM‐RA as an important prognostic marker (hazard ratio: 2.260, 95% confidence interval: 1.177–4.340, P = 0.014), myosteatosis lost its significance when early mortality (90 days) was excluded from the final multivariable model. Patients with myosteatosis showed significantly higher all‐cause mortality and in particular higher rates of deaths due to respiratory and septic complication ( P = 0.002, P = 0.022, and P = 0.049, respectively). Conclusions: Preoperative myosteatosis may be an important prognostic marker in patients undergoing deceased donor liver transplantation. The prognostic value of myosteatosis seems to be particularly important in the early post‐operative phase. Validation in prospective clinical trials is warranted.